THE EFFECT OF AN INSTRUCTION WORKSHEET WITH GUIDE INQUIRY DESIGN AND INTERVIEW CREATIVE THINKING TECHNIQUE ON CREATIVE THINKING SKILLS IN SENIOR HIGH SCHOOL STUDENTS - Nizar, M (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
This study aims at examining the effects of use of Interview technique and worksheets together on the subject of matter geometric optics of senior high school 11th grade students on the creative thinking skills. Simple experimental method was used in the present study. Study group of the research comprises of 108 11th grade students studying in public school in Balongpanggang district of East Java province. The prepared Test for Creative Thinking Skills and Interview Technique (TCT-IT) was administered to the students as pre-test-post-test. Data obtained via pre-test-post-test were transferred to SPSS 15.00 program was applied on these data. Frequency and percentage table was constituted. Considering the analysis results, it was concluded that use of worksheets and interview technique together has positive effects on students creative thinking skills